2017
DOI: 10.1111/obes.12163
|View full text |Cite
|
Sign up to set email alerts
|

Quantile Aggregation of Density Forecasts

Abstract: Quantile aggregation (or ‘Vincentization’) is a simple and intuitive way of combining probability distributions, originally proposed by S.B. Vincent in 1912. In certain cases, such as under Gaussianity, the Vincentized distribution belongs to the same family as that of the individual distributions and it can be obtained by averaging the individual parameters. This article compares the properties of quantile aggregation with those of the forecast combination schemes normally adopted in the econometric forecasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…The solid line represents the performance based on the quantile aggregation, which aggregates all forecasters in the pool. As found by other research papers, e.g., [2,3] the quantile aggregation method generates a decent predictive distribution, which performs slightly better than the ex-post top 4 forecaster. The right panel in Figure 1 shows the historical performance of our proposed approach with various choices of regularization parameter, γ.…”
Section: Empirical Illustrationsupporting
confidence: 77%
See 2 more Smart Citations
“…The solid line represents the performance based on the quantile aggregation, which aggregates all forecasters in the pool. As found by other research papers, e.g., [2,3] the quantile aggregation method generates a decent predictive distribution, which performs slightly better than the ex-post top 4 forecaster. The right panel in Figure 1 shows the historical performance of our proposed approach with various choices of regularization parameter, γ.…”
Section: Empirical Illustrationsupporting
confidence: 77%
“…In the univariate case, an equally weighted centroid defined by a Wasserstein metric corresponds to a quantile averaging or vincentized center where quantiles of forecast densities are averaged. The resulting combined density tends to be narrower than the linear opinion rule [1][2][3], which may or not be desirable, depending on the context.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Is it better to average quantiles (as in quantile averaging) or average probabilities (as in linear pooling)? By restricting themselves to simple averages, and Busetti (2017) theoretically and empirically compared the properties of these two combination strategies and suggested that quantile averaging seems overall a preferable and viable approach. attributed this, in part, to the fact that the average probability forecast is in general underconfident while the average quantile forecast is always sharper.…”
Section: Quantile Forecast Combinationsmentioning
confidence: 99%
“…Furthermore, an important note is the meaning of the word "probabilities" in the quantitative opinion combination literature. Whilst traditionally, "probabilities" means mass or density functions for the discrete case and continuous case, respectively Clemen (1989), in recent years, there has been some evidence that combining quantiles, first suggested by Vincent (1912), might be at least as good as combining probability densities (see Lichtendahl et al (2013), Busetti (2017), Bansal and Palley (2017), Hora et al (2013), Bogner et al (2017, and Jose et al (2013)), despite some criticism from Colson and Cooke (2017). Quantiles combination was also found to be preferable when individual forecasts are biased; see Bamber et al (2016) and Lichtendahl et al (2013).…”
Section: Quantitative Approachesmentioning
confidence: 99%